C++ plus data structures - Dale, Nell (Jones and Bartlett, 1999)
10 parts: Software engineering principles; data sesign and implementation; ADTS unsorted list and sorted list; ADTs stack and Queue; linked structures; lists plus; programming with recursion; ...